Partisipasi Masyarakat Dalam Pembangunan Fisik Desa - Rachaju, Kantirina; Hikmat, Asep; Abdurrahman, Maman (Jurnal Soshum Insentif, 2022)
The background of this research is the lack of awareness in the development of the surrounding environment, the lack of opportunities to express ideas, the lack of self-help in the form of funds, labor and materials. The purpose of this study is to obtain an overview of several factors that cause low participation, referring to Theresia's theory. et. al (2014) in Hajar (2018:32-34) namely community participation in development activities. The main premise: Physical participation will be successful if it is supported by the right decision making, optimal implementation, proper monitoring and evaluation, and adequate utilization of the results. Minor premise : Based on the research results, physical participation: decision making is not right, implementation is not optimal, monitoring and evaluation is not good, and utilization of results is not optimal. This research uses a qualitative approach with a descriptive study, conducted in the village of Curughurur Sagaranten, Sukabumi Regency. There were 5 informants using purposive sampling and snowball sampling. The objects in this study are: the Head of the BPD, the Village Head, the Head of the Activity Implementation Team (TPK), the Community. Collecting data through participatory observation; semi-structured interviews; documentation study using observation guides, interview guides, field notes; data validation using triangulation (technique, source, and time); and analyzed using reduction. Presentation of data and drawing conclusions.